Systemic Analysis of the Prognosis-Associated Alternative Polyadenylation Events in Breast Cancer - Zhang, Yi; Wang, Yuzhi; Li, Chengwen; Jiang, Tianhua (Frontiers in Genetics, 2020)
Alternative polyadenylation (APA) is a posttranslational modification that occurs during mRNA maturation in humans. Studies suggested that abnormal APA events are associated with the genesis and progression of malignant tumors. Here, we aimed to comprehensively evaluate the prognostic value of APA events involved in breast cancer (BC). Both APA events and clinical information for BC patients were downloaded from The Cancer Genome Atlas (TCGA) database to identify prognosis related APA events in BC. A total of 462 APA events and 374 APA events were shown to be significantly related to overall survival (OS) and relapse-free survival (RFS), respectively, of BC patients. The TCGA set was randomly divided into a training and test sets. Key prognosis-related APA events were selected by lasso regression to build prediction signatures for OS and RFS by multivariate Cox regression analysis in the training, test and whole set. BC patients were stratified into high-risk and low-risk groups based on median risk scores. Kaplan-Meier survival analysis demonstrated that low-risk groups had better OS and RFS than high-risk groups in all three sets. The time-dependent receiver operating characteristic (ROC) curves showed that our signatures had a good predictive ability for survival and recurrence for BC patients in all three sets. The independent prognostic indicators-based nomogram model had excellent performance and considerable net benefit for predicting the OS and RFS in BC. A PPI network was constructed between key prognosis and core regulators associated with APA, consisting of 48 nodes and 244 edges. Functional enrichment analysis also revealed their association with RNA processing, RNA synthesis. Collectively, our data indicate that prognostic signatures based on APA events may be powerful prognostic predictors for OS and RFS in BC.